Aspek Hukum Perdata dan Pidana dalam Kasus Kekerasan terhadap Pekerja Migran Indonesia yang Berdampak pada Kesehatan Mental dan Fisik - Cici Rifla; Heriyanto Saputra (Pagaruyuang Law Journal, 2026)
The issue of violence against Indonesian migrant workers continues to be a significant legal concern, particularly for those working in the domestic sector in Hong Kong. Acts of physical, mental, sexual, and economic violence not only violate criminal and civil law but also impact the health and well-being of the victims. This study aims to evaluate criminal and civil legal protections for Indonesian migrant workers who are victims of violence and to assess the effectiveness of online legal and health education in raising awareness of their legal rights. The study employs an empirical legal method with a socio-legal approach through legal analysis and data collected from virtual educational sessions via Zoom with Indonesian migrant workers in Hong Kong. The findings indicate that legal protections are available in various national and international legal instruments; however, their implementation still faces obstacles such as low legal literacy, limited access to legal aid, fear of reporting, and a lack of knowledge regarding mental health recovery. Online legal and health education has proven to help improve migrant workers’ understanding of their legal rights, reporting mechanisms, and recovery efforts. These findings indicate that comprehensive legal protection and sustained digital education are necessary to strengthen access to justice and protection for Indonesian migrant workers.